Cognitive and language deficits in persons with Parkinson's disease - Vuković Mile G. (Univerzitet u Beogradu - Fakultet za specijalnu edukaciju i rehabilitaciju, 2021)
Introduction. Contemporary research of Parkinson's disease increasingly emphasizes the importance of various non-motor signs, including cognitive and language deficits. This is a significant shift from previous research which focused primarily on the study of motor disorders. Objective. This article aims to systematically present and analyse contemporary empirical data on the presence of language and cognitive deficits in Parkinson's disease. Studies on the assessment and treatment of cognitive and language functions are also mentioned. Methods. Various electronic databases of Serbian libraries and specialized Internet search engines were used to search for relevant literature. Descriptive, analytic and synthetic methods were used. Results. The empirical data show that cognitive disorders can be observed in the initial stages of the disease and that they become more pronounced with disease progression. Cognitive deficits are manifested in the domains of executive functions, visuospatial abilities, attention, and memory. Studies devoted to the study of language testify to the manifestation of deficits in all language skills. Language and cognitive disorders, associated with dysarthria and deficits in nonverbal communication, negatively affect communication skills, and the patient's life quality. Conclusion. Cognitive decline in Parkinson's disease ranges from mild cognitive impairment to severe dementia. Language disorders are manifested in auditory comprehension, spontaneous speech, naming, repetition, discourse, reading, and writing. For treating cognitive and language deficits, a pharmacological and nonpharmacological approaches are used. The goal of speech-language therapy, as a part of nonpharmacological approach, is to slow down progression of cognitive and language disorders, maintain communicative abilities, and compensate for deficits.